Pengaruh Prosedur Pajak, Dan Kemandirian Wajib Pajak Terhadap Kepatuhan Pajak UMKM Di Kota Bandung - Amzad Wahdaniel Fayaadh; Renata Iswara; Felix Aditya Firmansyah; Salsa Ayu Nurfaiza; Abrar Rabbani; Desty Nismalasari; Mochamad Syachrial Azman (GLOBAL SCIENTS PUBLISHER, 2026)
Tax compliance among micro, small, and medium-sized enterprises (MSMEs) is a key factor in enhancing local tax revenue. In practice, however, several challenges affect MSME compliance, particularly in terms of their understanding of tax procedures and their ability to fulfill tax obligations independently. This study seeks to examine how tax procedures and taxpayer autonomy influence tax compliance among MSMEs in Bandung City. This research adopts a quantitative approach, utilizing a questionnaire survey to collect data from MSME stakeholders in Bandung. A purposive sampling technique was applied to select a total of 46 respondents. Data analysis was conducted using SPSS statistical software The findings indicate that tax procedures have a positive and significant effect on MSME tax compliance, contributing (…%) to the outcome. Similarly, taxpayer autonomy also demonstrates a significant positive impact, with a contribution of (…%). When examined simultaneously, both tax procedures and taxpayer autonomy collectively exert a significant influence on MSME tax compliance, with a coefficient of determination (R² = …) of …. These results provide insights for tax authorities in designing policies aimed at simplifying tax procedures and fostering greater independence among MSME taxpayers.